Comprehensive Analysis of The Role of Nursing in Promoting Healthcare Equity - ALRuwaili, Ahlam Ramdan; Alrowaili, Tahrer Eid Mahammd; Alanazi, Noha khalaf; Alanazi, Bedoor khalaf; Al Rowaili, Emtthal Wanes; Alotaibi, Maitha habab; Alrewaili, Maha Zaben; Aldhafiri, Azeza saber; Alshammari, Mariam Nhiter; Aldossary, Alhanoof M Arzooq (Journal of Ecohumanism, 2024)
Nursing’s contribution to healthcare equity is a component of the continual transformation of healthcare systems worldwide. Nurses, being in the most direct touch with the patient and responsibilities involved in multiple activities related to patient care, are well poised to perceive and respond to inequalities in healthcare access, provision, and utilization. Hence, the following paper describes the extent of nursing involvement and contribution to advancing healthcare equity, especially amongst vulnerable groups. Each strategy focuses on exploring the theories that enhance nursing approaches to social determinants of Health, cultural competency, and approaches to advocacy for effective health equity. Further, it examines how nursing education, workforce diversity, policy reform, and nursing can improve equity within a healthcare system. These insights support further and sustained reform of the system and nursing advocacy movements working toward the development of equal care for all.